Analisis Krisis Keuangan ASIA 1997: Penyebab, Dampak, dan Pemulihan Ekonomi di Indonesia - Rifadli D. Kadir (Scimadly Publishing, 2025)
The 1997 Asian financial crisis had a profound impact on the economies of Asian countries, including Indonesia. The crisis began with the depreciation of Thailand's Baht, which spread to neighboring countries, destabilizing the economies of Indonesia, Thailand, and South Korea. A sharp decline in currency values, high interest rates, and a banking crisis led to economic uncertainty across sectors. The primary cause of the crisis was the